What we do in the shadows [videorecording (DVD)] - Clement, Jemaine; Waititi, Taika; Brugh, Jonathan (Paramount Pictures Corporation, 2015)
Vulvus, Viago, and Deacon are vampires who live here, among us. They are real vampires; undead, immortal creatures who stalk the night and search for human blood, preferably virgins. Witness the many horrid, abominable aspects of vampire life, such as hunting and feeding, vampire rivalry and fighting with werewolves, as well as normal night to night aspects that make them not so different from us like keeping the flat clean, jobs, shopping, meeting people and trying to fit in.